(untitled) (Homoeopathy for All, 2024)
Now-a-days, the public acceptance of Homoeopathy is gaining momentum in view of its harmlessness, easy affordability and accessibility, safety, efficacy, and gentle method of administration of medicines. Due to the increasing health challenges in our country, the Govt. of India have adopted the principle of “medical pluralism”, giving more focus on Complementary & Alternative Medicines (CAM) including Homoeopathy. The Ministry of Ayush, Govt. of India have also been encouraging the public to opt health care service of their choice, through the cafeteria mode.